Pío peep! : traditional Spanish nursery rhymes - Ada, Alma Flor; Campoy, F. Isabel; Schertle, Alice; Escrivá, Viví (HarperCollins, 2003)
A collection of more than two dozen nursery rhymes in Spanish, from Spain and Latin America, with English translations.